Advanced High Strength Steel Processing and Applications - Roy, Tapas Kumar; Bhattacharya, Basudev; Ghosh, Chiradeep; Ajmani, S. K.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This volume comprises select proceedings of the AHSS 2017 conference. AHSS is an instrumental event in creating a platform for exchanging recent thoughts and results among a selective group of researchers working in the area of steel science and engineering. Twenty four papers selected papers have been included in this volume. This book will serve as a reference book to many practitioners and researchers working in the areas of steel strength, characterization, and applications. .
Paper 1: Dynamic transformation during the Torsion simulation of plate and strip rolling -- Paper 2: Microstructure Engineering of High Performance Steels -- Paper 3: Recent topics on development of automotive high strength sheet steels -- Paper 4: An overview on structure property relationship of TRIP aided steel -- Paper 5: Industrialization, mechanical properties and applications of a new stainless TWIP-steel -- Paper 6: Evolution of texture in some Mn steel -- Paper 7: Development of advanced high strength steel for lifting and excavation sector at ESSAR Steel -- Paper 8: High Strength Linepipe Steels and Physical Simulation of Production Processes -- Paper 9: Recent Advances in Welding of High Strength Bainitic Steel for Automotive Applications -- Paper 10: Mechanical properties of copper added ultrafine bainitic steel -- Paper 11: Microstructure based deformation modelling of Dual Phase Steels -- Paper 12: Effect of Flash Annealing on Bulk Nanostructured Low Carbon Steel Processed through Equal-channel Angular Pressing followed by Cryorolling -- Paper 13: Microstructural evolution in boron added advanced high strength steel suitable for hot stamping -- Paper 14: A novel low carbon high strength steel: processing, microstructure and mechanical properties -- Paper 15: Recrystallization texture evolution in HSLA steel -- Paper 16: Technological Challenges and Solutions for the Production of state of the art 2nd and 3rd generation AHSS Grades -- Paper 17: Gas-liquid flows in ladle shroud and their impact on tundish process performance and steel quality -- Paper 18: Novel casting technology preventing slab transverse corner cracks of typical micro-alloyed steels -- Paper 19: Non-metallic particles benefit or burden for AHSS? -- Paper 20: Advanced High Strength Steel - Challenges to a Steelmaker -- Paper 21: Macro-segregation of multicomponent steel in round billet continuous caster -- Paper 22: Production of high strength plates through new plate mill at RSP.
Keywords: Metals; Manufactures; Materials; Metals and Alloys; Machines, Tools, Processes; Materials Engineering